2006
DOI: 10.1097/01.gim.0000217781.66786.9b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maltose and acarbose as inhibitors of maltase-glucoamylase activity in assaying acid α-glucosidase activity in dried blood spots for the diagnosis of infantile Pompe disease

Abstract: Purpose: The study's purpose was to compare acarbose and maltose as inhibitors of maltase-glucoamylase activity for determining acid ␣-glucosidase activity in dried blood spot specimens for early identification of patients with infantile Pompe disease, a severe form of acid ␣-glucosidase deficiency. Methods: Acid ␣-glucosidase activities in dried blood spot extracts were determined fluorometrically using the artificial substrate 4-methylumbelliferyl-␣-D-pyranoside. Acarbose or maltose was used to inhibit malta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 14 publications
(11 reference statements)
0
44
0
Order By: Relevance
“…With the fluorogenic substrate 4-methylumbelliferyl-␣-glucoside, acarbose concentrations of 3-9 mol/L are sufficient to inhibit maltase glucoamylase activity in the assay (8,9 ). We found that with the synthetic substrate in this assay, 8 mol/L acarbose provided sufficient inhibition of maltase glucoamylase and maintenance of GAA activity (Supplemental Fig.…”
mentioning
confidence: 77%
“…With the fluorogenic substrate 4-methylumbelliferyl-␣-glucoside, acarbose concentrations of 3-9 mol/L are sufficient to inhibit maltase glucoamylase activity in the assay (8,9 ). We found that with the synthetic substrate in this assay, 8 mol/L acarbose provided sufficient inhibition of maltase glucoamylase and maintenance of GAA activity (Supplemental Fig.…”
mentioning
confidence: 77%
“…Individual 3-mm DBS punches obtained from NBS cards and DBS cards from the control and patient groups were assayed for Pompe and Fabry diseases using benchtop fluorometry methods previously described (7,8,15,21 ). All procedures were carried out according to standard operating procedures in the Duke BGL, which is a College of American Pathologists (CAP) and Clinical Laboratory Improvement Amendment (CLIA) certified clinical laboratory.…”
Section: Protocols For the Benchtop Fluorometric Enzyme Assaysmentioning
confidence: 99%
“…Other state programs (in Illinois, Missouri, and New Mexico) have recently mandated screening for certain LSDs. Using a modified version (15 ) of the fluorometric assay introduced by Chamoles et al (8 ), the NBS program in Taiwan has screened 206 088 newborns for Pompe disease (16 ) and 171 977 for Fabry disease (17 ). A recently published review article provides a nice overview of the current state of NBS for LSDs (18 ).…”
mentioning
confidence: 99%
“…49 -51 GAA activity can be either measured using fluorometry or tandem mass spectrometry (MS/MS). 49,50,52,53 Although there is a correlation between GAA activity in fibroblasts and clinical phenotype, the clinical phenotype may not be readily predicted through enzyme analysis in different tissues. 54 Serum creatine kinase, transaminases, and lactate dehydrogenase are increased in most patients with PD but may occasionally be within normal limits in those with adult-onset PD.…”
Section: Introductionmentioning
confidence: 99%